PERTIMBANGAN BERHUNI PADA PERMUKIMAN KAMPUNG DI KOTA MALANG - Nazaruddin, A. Farid (RUAS (Review of Urbanism and Architectural Studies), 2017)
City Kampung settlements usually unfavorable as a settlements, mostly by general perspective that kampung are â€œpoor peopleâ€ settlements, or not modern and not organized. In addition, it is not suitable to own a car and to be put in site (as would normally Indonesian people do), because of the really narrow streets in kampung. Thus, it should making them as settlements to be avoided. Especially by the so-called rich people. This Paper presents a result on preliminary research on those â€œrichâ€ people about why one move or live in Kampung Settlements if they can afford to move away. The research conducted at all the expensive houses in Kampung Kauman, Kampung Gandekan, Kampung Tongan, kampung Sawahan and Kampung Arab in Malang City Indonesia. Samples are chosen by the researcher general assessments on its expensiveness and that the house is at the narrow streets of the Kampung. The Method used are in-depth interviews to know their considerations on each Samples. The Results that the basic factor for consideration on living in kampung settlements (even though they can afford to move away) is because of the atmosphere of Kampung neighborhood it self.Â